Acceptability, feasibility, and pilot results of the tele-harm reduction intervention for rapid initiation of antiretrovirals among people who inject drugs. (1st December 2021) - Tookes, Hansel E.; Bartholomew, Tyler S.; Suarez, Edward; Ekowo, Elisha; Ginoza, Margaret; Forrest, David W.; Serota, David P.; Rodriguez, Allan; Kolber, Michael A.; Feaster, Daniel J.; Mooss, Angela; Boyd, Derek; et al.
Abstract: Background: People who inject drugs (PWID) have been a marginalized and a stigmatized population since the beginning of the AIDS epidemic and have not experienced the same life-changing benefits of antiretroviral therapy as others. Tele-Harm Reduction ( THR ) is a telehealth-enhanced, harm reduction intervention, delivered within a trusted SSP venue. It aims to facilitate initiation of care and achieve rapid HIV viral suppression among PWID living with HIV. Methods: In this mixed-methods study, we employed the Practical, Robust, Implementation and Sustainability Model (PRISM) implementation science framework to identify multilevel barriers and facilitators to implementing the THR intervention. Focus groups (n = 2, 16 participants), stakeholder interviews (n = 7) and in-depth interviews were conducted with PWID living with HIV (n = 25). In addition, to assess feasibility and acceptability, we pilot tested the THR intervention and reported viral suppression at 6 months. Results: Focus groups and stakeholder interviews revealed system and organizational level barriers to implementation including requirements for identification and in person visits, waiting times, stigma, case management inexperience, multiple electronic health records, and billing. A potential facilitator was using telehealth for case management and initial provider visit. In the in depth interviews conducted with PWID living with HIV, participants expressed that the SSP creates a convenient, comfortable, confidential environment for delivering multiple, non-stigmatizing PWID-specific services. 35 PWID living with HIV were enrolled in the pilot study, 35 initiated antiretroviral therapy, and 25 (78.1%) were virally suppressed at six months. Conclusion: Rooted in harm reduction, the THR intervention shows promise in being an acceptable and feasible intervention that may facilitate engagement in HIV care and viral suppression among PWID. Highlights: Tele-Harm Reduction is a peer driven, telehealth enhanced, harm reduction intervention. Tele-Harm Reduction overcomes stigma and meets persons who inject drugs where they are. Tele-Harm Reduction is promising in supporting HIV viral suppression.